Impact of health education on knowledge, attitude and practices about menstrual hygiene among adolescent girls of a college in Vijayapura - Janvekar, Sadafara S.; Doddihal, Chandrika R.; Pattankar, Tanuja P. (International Journal Of Community Medicine And Public Health, 2022)
Background: Menstrual hygiene is an issue that is inadequately recognized. Lack of privacy and sanitation for the adolescent girls make them susceptible for physical and psychological problems especially during the days of menstruation. Education about menstrual hygiene is a vital aspect for the wellbeing of the adolescent girls. Methods: Pre and post-test was done regarding the knowledge, attitude and practice of the Adolescent girls towards the menstrual hygiene. Results: Total of 68 adolescent girls studying in Pre university were enrolled in the study which was conducted for the period of 5months from March to July 2019. Mean age of the participants was 16.5years. 89.7% were residents of Urban area. In our study, we found that they were not properly maintaining the menstrual hygiene. Only 88% of girls knew that menstruation is a physiologic process, 37% knew that menarche is caused by hormones. 85% of them used the pads during the menstruation but 15% disposed it unhygienically. Conclusions: Embracing high quality menstrual hygiene will play an important role in prevention of reproductive Tract Infection, pelvic inflammatory diseases and Cancer of cervix among the women population. Therefore, endorsing positive approach towards management of menstruation and related problems among the adolescents is the need of the hour.